Acute Respiratory Failure. (5th September 2018) - Cannon, Jeremy; Pamplin, Jeremy; Zonies, David; Mason, Phillip; Sine, Christy; Cancio, Leopoldo; McNeill, Jeffrey; Colombo, Christopher; Osborn, Erik; Ricca, Robert; Allan, Patrick; DellaVolpe, Jeff; et al.
Abstract: Acute respiratory distress syndrome (ARDS) is a condition affecting critically ill patients, characterized by pulmonary inflammation and defects in oxygenation due to either direct or indirect injury to the lungs. These guidelines will define the diagnosis and management of ARDS, particularly among combat casualties and patients in the deployed environment. The cornerstone of management of ARDS involves maintaining adequate oxygenation while avoiding further pulmonary injury through lung-protective ventilation. Additional strategies for advanced respiratory failure, such as prone positioning, neuromuscular blockade, and extracorporeal membrane oxygenation will be reviewed here as well. Particularly important to the care of the patient with ARDS in the deployed environment is a familiarity with the challenges and indications for transport/aeromedical evacuation.